2004
DOI: 10.1103/physrevlett.92.127404
|View full text |Cite
|
Sign up to set email alerts
|

Rabi Flopping in a Two-Level System with a Time-Dependent Energy Renormalization: Intersubband Transitions in Quantum Wells

Abstract: We obtain pulse-driven Rabi oscillations guided by a generalization of the rotating-wave approximation to include, in the optical-Bloch equations, two-level systems with a time-varying transition energy. We achieve this by using chirped pulses with the central frequency given by the time-varying transition energy. Using this approach, we predict Rabi oscillations in intersubband transitions in a two-subband n-type modulation-doped quantum well by taking into account the time-dependent intersubband energy-gap r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 20 publications
0
34
0
2
Order By: Relevance
“…However, one can use pulses that are suitably chirped to compensate for a change of frequency of the optical transition in time induced by the pulses themselves. This idea was proposed in studies of a two-state system in relation to Rabi oscillations in inter-subband transitions in quantum wells 21 and for obtaining efficient stimulated Raman adiabatic passage in molecules in a dense medium. 19 Let us suppose that we use suitably chirped pulses compensating the "local field" detuning pDn that enables us to keep the value of x 21 À pDnðtÞ À xðtÞ Dx as a constant.…”
Section: 18mentioning
confidence: 99%
“…However, one can use pulses that are suitably chirped to compensate for a change of frequency of the optical transition in time induced by the pulses themselves. This idea was proposed in studies of a two-state system in relation to Rabi oscillations in inter-subband transitions in quantum wells 21 and for obtaining efficient stimulated Raman adiabatic passage in molecules in a dense medium. 19 Let us suppose that we use suitably chirped pulses compensating the "local field" detuning pDn that enables us to keep the value of x 21 À pDnðtÞ À xðtÞ Dx as a constant.…”
Section: 18mentioning
confidence: 99%
“…Unbound excitations, ISBTs have a narrow absorption line thanks to the fact that conduction subbands are quasi-parallel [23,24] (see Fig. 2 (a) for a graphical representation).…”
mentioning
confidence: 99%
“…In recent years, Rabi flopping and coherent propagation of ultrashort electromagnetic pulses have been studied both theoretically and experimentally when intersubband transitions of semiconductor quantum wells interact with electromagnetic fields [1,2,3,4,5,6,7,8,9]. In some of these studies the Rabi flopping [2,3,8] and the coherent propagation of ultrashort far-infrared electromagnetic pulses [4,5,7] that interact with a two-subband system in a symmetric semiconductor quantum well structure, taking into account the effects of electronelectron interactions, have been presented.…”
Section: Introductionmentioning
confidence: 99%
“…In some of these studies the Rabi flopping [2,3,8] and the coherent propagation of ultrashort far-infrared electromagnetic pulses [4,5,7] that interact with a two-subband system in a symmetric semiconductor quantum well structure, taking into account the effects of electronelectron interactions, have been presented. All these studies have shown that at certain electron densities the electron-electron interactions make the intersubband transitions to behave quite differently from atomic transitions.…”
Section: Introductionmentioning
confidence: 99%